Desain Animasi Sejarah Kapel Santa Maria dari Betlehem (Gereja Karmel Lembang) - Tonalou, Paskalis Daniel; Albar, Deni (Fakultas Desain Universitas Komputer Indonesia, 2022)
There are many houses of worship built during the colonial period in Bandung and the buildings have a historical story behind it. Some of the history of worship houses are not published in public so many people do not know about it. One of them is the St. Maria from Bethlehem Chapel or known as the Lembang Carmel Church. Not many people, especially the people of this church, know about the history of the founding of this church, even though previously there were books that discussed it. This is because the book is exclusive and not everyone has it. With the people knowing the history of their church, it is hoped that the people will love their church, a sense of belonging will arise, and people know what spirit the pioneers brought to build churches. So, design was made to tell the history of the Chapel of St. Maria from Bethlehem (Lembang Carmel Church) by presenting a unique visual through Wayang Kulit, so the people are interested in knowing it. Video Animation is the main media in this design, animated video contains images and sounds that are mixed to make the main media more attractive. The main media is distributed through Youtube platform so it hoped the design will reach the audience easily.